Communicating a Model-Based Energy Performance Indicator. (October 2014) - Hilliard, Antony; Jamieson, Greg A.; Jorjani, David
Monitoring energy performance can help organizations make better efficiency investment and operational decisions. However, key energy performance indicators can be difficult to interpret because they blend effects of real system changes and statistical model behavior. We designed an explanatory energy model report for a commercial energy-monitoring product. The design was guided by a task analysis based on user observation, interviews, and designer participation. It was refined with usability heuristics, task walk-throughs, and tabletop discussions. Our collaborator is incorporating the design into its next product revision.